Bioinformatic analysis of genotype by sequencing (GBS) data with NGSEP - Perea, Claudia Samantha; Hoz, Juan Fernando de la; Cruz, Daniel Felipe; Lobaton, Juan David; Izquierdo, Paulo; Quintero, Juan Camilo; Raatz, Bodo; Duitama, Jorge (Springer, 2016)
Background Therecent development and availability of different genotype by sequencing (GBS) protocols provided a cost-effective approach to perform high-resolution genomic analysis of entire populations in different species. The central component of all these protocols is the digestion of the initial DNA with known restriction enzymes, to generate sequencing fragments at predictable and reproducible sites. This allows to genotype thousands of genetic markers on populations with hundreds of individuals. Because GBS protocols achieve parallel genotyping through high throughput sequencing (HTS), every GBS protocol must include a bioinformatics pipeline for analysis of HTS data. Our bioinformatics group recently developed the Next Generation Sequencing Eclipse Plugin (NGSEP) for accurate, efficient, and user-friendly analysis of HTS data.